The influence of safety management practices on safety performance among staff aluminium company of Malaysia Berhad - Azahara, Abdul Abbas (2020)
Safety management practices plays the crucial roles for accident prevention program at workplace. It also influenced employee attitude and behavior towards safety directly and indirectly. This study aims to access relationship between safety management practices and safety performance. The survey applied the self-administrative questionnaires involved 307 employees who are employment in Aluminium Company of Malaysia Berhad at Klang Selangor. The raw data was analyzed with using Statistical Package for Social Package (IBM SPSS Statistics 25.0) and descriptive and inferential analysis was conducted to fulfill the objective of study. Correlation analysis show the strong relationship between the safety management practices and safety performance. Furthermore, regression analysis shows there are two dimension of safety management practices were significant relationship between safety performance which were management commitment and safety rules and procedures. The findings of this study has benefited the company to identify the most significant practice to enhance the safety performance and accident prevention programmed.